1987
DOI: 10.1007/bf01297192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of misoprostol on histamine-stimulated acid secretion and cyclic AMP formation in isolated canine parietal cells

Abstract: Isolated canine parietal cells were used to study the ability of misoprostol to inhibit acid secretion in the presence of a number of acid secretagogues. Misoprostol inhibited histamine-stimulated acid secretion in a dose-dependent and noncompetitive manner. A concentration of 2-3 X 10(-9) M misoprostol inhibited maximal histamine-stimulated acid secretion by one half. Misoprostol had little to no effect on acid secretion stimulated by carbachol and dibutyryl cAMP, had no effect on the acid secretion directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The EP 3 receptor has at least four splicing variants coupled with different signaling pathways (14). It has also been reported that PGE 2 and its analog inhibited acid secretion as well as cAMP production stimulated by histamine in parietal cells (27,35). In addition, activation of the EP 3D receptor causes an elevation of intracellular Ca 2ϩ by stimulating G q protein.…”
Section: Discussionmentioning
confidence: 99%
“…The EP 3 receptor has at least four splicing variants coupled with different signaling pathways (14). It has also been reported that PGE 2 and its analog inhibited acid secretion as well as cAMP production stimulated by histamine in parietal cells (27,35). In addition, activation of the EP 3D receptor causes an elevation of intracellular Ca 2ϩ by stimulating G q protein.…”
Section: Discussionmentioning
confidence: 99%
“…Natural and synthetic PGs have been shown to be potent inhibitors of gastric acid secretion and offer protection against peptic ulcers in animals and humans (26)(27)(28)(29)(30)(31). PG induced cytoprotective effects may involve increased blood flow (32,33), bicarbonate secretion (34), mucus release (35), restoration of active sodium transport (36), decrease in back diffusion of acid or local stimulation of surface-active phospholipids (37), and maintenace of normal mucosal levels of DNA, RNA or protein (38).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins are synthesised by the gastric mucosa and considered necessary for mucosal protection (Wilson 1996). By direct action on parietal cells, misoprostol inhibits gastric acid secretion, both basally and that stimulated by food, pentagastrin or histamine (Tsai et al 1987). Misoprostol also has a cytoprotective effect on gastric mucosa, although the mechanism is not clear: it is postulated to result from increased production of gastric mucus and bicarbonate, and increased turnover and blood supply of gastric mucosal cells (Tsai et al 1987), which theoretically contributes to ulcer healing.…”
Section: Misoprostolmentioning
confidence: 99%